Satisfaction Levels of Sport Sciences University Students in Online Workshops for Substituting Practice-Oriented Activities during the COVID-19 Lockdown - Enzo Iuliano; Massimiliano Mazzilli; Stefano Zambelli; Filippo Macaluso; Paolo Raviolo; Pietro Picerno (Education Sciences, 2021)
Laboratory teaching in sport and exercise sciences universities is of fundamental importance as it provides students with the necessary hands-on skills that are indispensable to future kinesiologists. However, due to the COVID-19 pandemic, students in lockdown missed the opportunity to acquire laboratory skills. Here we report the solutions adopted by a blended exercise science Master’s degree program of an online Italian university to ensure didactic continuity in the practice-oriented activities during the period of the COVID-19 lockdown. In order to mitigate this issue, laboratory sessions were replaced with online workshops and students’ satisfaction levels in this regard were investigated in the present study using an online survey conducted on 101 students during lockdown. The survey consisted of 7-point Likert scale items focusing on computer usage (CU), learning satisfaction (LS), social interaction (SI), and perceived value (PV). The analysis of the results revealed a good level of learning satisfaction of the students. Conversely, students perceived a moderate level of social interaction and had a moderate perception that online workshops can enhance their learning abilities. In conclusion, the results of the present study seem to indicate that online workshops can be considered a good and acceptable compromise during an emergency, although face-to-face activities remain the preferable learning delivery modality when dealing with the acquisition of hands-on skills.